Pemanfaatan Limbah Sampah Anorganik dari Kaleng Bekas sebagai Peluang Usaha di Pahandut Seberang Kota Palangka Raya - Ghina Muslimah, Nur; Ariana, Eva; Taybah, Siti (LP2M IAIN Sultan Amai Gorontalo, 2021)
Creativity is a process that demands balance and application of the three essential aspects, namely analyst intelligence, creativity and practice. One of the benefits of creativity is that it eliminates what everyone doesn't like, namely problems. Creativity that exists in the individual can build business opportunities. Business opportunity is an application that consists of creativity and innovation to solve problems and see the opportunities faced every day. In this service program, what is being carried out is training to increase the creativity of Kertanel handicrafts (KERTANEL). The approach method used is Asset Based Community Development (ABCD). The concept of Asset Based Community Development or the term “ABCD” is one strategy in carrying out community development. In the concept of empowerment, the community that is the target of empowerment is no longer called a weak group and does not have any potential. On the contrary, the community is seen as a group that actually has the potential to get out of various problems, including the problem of improving the standard of living, socio-economy.